Rancang Bangun Sistem Arsip Surat Berbasis Web Menggunakan Metode Waterfall Pada Pergerakan Mahasiswa Islam Indonesia(PMII) Komisariat Universitasitas Nahdlatul Ulama Kalimantan Selatan - Risdayati, Sunni; Mawaddah, Nurul (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2025)
The Indonesian Islamic Student Movement (PMII) South Kalimantan Nahdlatul Ulama Commissariat is a student organization that is actively involved in various academic and non-academic activities. One of the basic needs of this organization is to manage mail archives efficiently and regularly. This research aims to design and develop a web-based letter archive system that can help PMII in managing letter archives more effectively. The method used in this research is the Waterfall method, which involves several stages, namely requirements analysis, system design, implementation, testing and maintenance. At the needs analysis stage, user needs and system specifications to be built are identified. Next, system design is carried out which includes designing the database, interface and system workflow. The implementation stage is carried out by building a system using the PHP programming language and MySQL database. System testing is carried out to ensure the system runs according to predetermined specifications. Finally, the maintenance stage is carried out to ensure the system continues to function properly and make repairs if errors are found. This system is expected to increase the efficiency and effectiveness of managing letter archives at PMII Nahdlatul Ulama Commissariat, South Kalimantan.